The Effect of Polypropylene Fiber and Steel Fiber on Geopolymer Concrete - Widiana, Niza; Satyarno, Iman; Siswosukarto, Suprapto (Jurnal Teknik Sipil dan Perencanaan, 2023)
One of the environmentally friendly concrete as an alternative to cement concrete in the future is geopolymer concrete which used a cement substitute in the form of fly ash. To prevent premature cracking of the concrete, this study added fiber types such as polypropylene fiber, and steel fiber (dramix), this experiment with 3 variables namely the addition of polypropylene fiber by 0%, 0.40%, 0.80%, 1.2%, steel fiber of 0.25%, 0.50%, 0.75%, 1.00%, as well as a combination of polypropylene fiber and steel fiber (0.4%P;0.50%D), (0.8%P;0.75%D), (1.2%P;1.00%D) of the weight of the concrete. In this study, using a beam specimen measuring 10x10x50 cm, for each percentage of fiber usage there are 2 beam trials. Geopolymer concrete in this study uses a ratio of NaOH and Na2SiO3 is 2:1 and a constant concentration of 10 Molar, to test the Flexural Strength Test of Concrete at the age of 28 days of concrete. The results of the highest average flexural strength of geopolymer concrete without fiber σl = 78.77 kg/cm2, using polypropylene 0.80% σl =50.50 kg/cm2, and 0.25% steel fiber σl =68.87 kg/cm2, the combination of both fibers (P0.4%; D0.25%) σl =65.34 kg/cm2. These results do not produce good workability, thus affecting the decrease in flexural strength. By increasing the ratio A = 0.35 to 0.45, the geopolymer concrete mix produces better workability with the highest average flexural strength of geopolymer concrete with polypropylene fiber 0.8% σl = 80.107 kg/cm2.